Analisis Risiko K3 Dengan Menggunakan Metode Hazard Identification, Risk Assessment and Risk Control (HIRARC) Pada Gedung HDI Hive Menteng - Danang Hadi Wibowo; Nova Pangastuti; Sepriandi Parningotan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The high competition in the property industry requires companies to maintain high occupational safety and health (K3) standards. Data from the engineering division of PT Gaia Care International shows that in the period January-November 2023 there were 11 work accidents, with the majority being minor accidents and one fatal case. This study aims to identify potential risk hazards, analyze risk levels, and determine appropriate risk control measures. The HIRARC method is used in three stages: Hazard Identification, Risk Assessment, and Risk Control. The results showed that there were various potential hazards such as electrocution, falling from stairs, and exposure to chemicals. The risk assessment classified 5 work activities as low risk, 43 as medium risk, and 2 as high risk and no extreme risk was found. Risk control efforts are carried out using fishbone diagrams and 5W+1H techniques to reduce or eliminate existing risks. This research is expected to provide benefits for companies in reducing the number of work accidents and become a reference in implementing better OHS policies, as well as providing additional insight for readers regarding the importance of risk analysis in creating a safe and healthy work environment.